Continuum Paradigm: Synchronization of Learning Process Elements (Models, Strategies, Methods, Approaches) Based on Problems from Basic Inquiry to Reog Ponorogo Culture-Based Industry Competencies in Generation Z and Alpha - Sulistyoningsih, Sulistyoningsih; Handayanah, Erna; Nurjanah, Sanita; Sumaji, Sumaji (Universitas Pahlawan Tuanku Tambusai, 2026)
The transformation of 21st-century education demands a continuous and contextual learning approach that aligns with the characteristics of Generation Z and Generation Alpha students. However, learning practices across educational levels remain fragmented, resulting in unsystematic development of student competencies. This study aims to examine the continuum paradigm in synchronizing problem-based learning from elementary to vocational high school levels by utilizing the local culture of Reog Ponorogo as a learning context. This research employed a descriptive qualitative approach through literature review, curriculum document analysis, and contextual observations in Ponorogo Regency. The findings indicate that the continuum paradigm enables the progressive development of student competencies, starting from basic inquiry skills in elementary school, strengthening critical and analytical thinking in high school, and applying practical competencies aligned with local culture-based creative industries in vocational high school. The main output of this study is a conceptual continuum framework that synthesizes learning models, strategies, methods, and problem-based learning approaches across educational levels within a local cultural context. The integration of Reog Ponorogo into problem-based learning enhances learning relevance, strengthens cultural identity, and supports student readiness for workforce demands. This study is expected to serve as a conceptual reference for the development of sustainable and integrated local culture-based learning designs.